Influencia de la violencia familiar en el rendimiento escolar de estudiantes de 6t0 año de primaria del i.e. carlos gutierrez noriega del distrito san pedro de lloc en el año 2013 - Llanos Cruz, Juliana Milagros (2014)
This thesis was conducted for the purpose of domestic violence affects school performance of students from primary 6toaño IE Carlos Gutiérrez Noriega of San Pedro de Lloc District in 2013 Applied research, in which we worked with descriptive, using methods and techniques of quantitative and qualitative research, a sample of 20 students / as, with the aim of demonstrating that the Family Violence creates a hostile and unstable climate, neglect parental and affects the emotional state and the students of the 6th year of Primary IE Carlos Gutiérrez Noriega of San Pedro de Lloc, 2013 Domestic violence, from a theoretical and scientific perspective is based on the social, educational and legal areas with a broad conceptual overview of different contemporary authors and supporting electronic documents and new information and communication technologies. The results show that the population studied, 70% had poor school performance; students indicate that parents use violence in their family; 60% have been assaulted by their parents; noting that the most frequent type of violence in their family discussion and verbal offense. Testimonies evident in the experiences of students and the influence and consequences that affect reproduction or the restriction of a harmonious and healthy development. So it is concluded that domestic violence affects produced poor academic performance, self-esteem and overall development of these children.